2020
DOI: 10.3390/ijms21197250
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Mouse Models of Abdominal Aortic Aneurysm Rupture

Abstract: Abdominal aortic aneurysm (AAA) rupture is an important cause of death in older adults. In clinical practice, the most established predictor of AAA rupture is maximum AAA diameter. Aortic diameter is commonly used to assess AAA severity in mouse models studies. AAA rupture occurs when the stress (force per unit area) on the aneurysm wall exceeds wall strength. Previous research suggests that aortic wall structure and strength, biomechanical forces on the aorta and cellular and proteolytic composition of the AA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 113 publications
0
18
0
Order By: Relevance
“…In this study, TUNEL staining and Annexin V-FITC/PI analysis results also demonstrated that NET treatment increased VSMC apoptosis via p38/JNK pathway. ECM degradation causes elastin degradation, thereby impairing aortic strength and elasticity (36). MMPs contain several members implicated in AAA formation.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, TUNEL staining and Annexin V-FITC/PI analysis results also demonstrated that NET treatment increased VSMC apoptosis via p38/JNK pathway. ECM degradation causes elastin degradation, thereby impairing aortic strength and elasticity (36). MMPs contain several members implicated in AAA formation.…”
Section: Discussionmentioning
confidence: 99%
“…Constructing a simple and reliable animal model of AAA provides a theoretical and practical basis for studying the pathogenesis and treatment of AAA. The animal models of AAA can be divided into three categories: physical, chemical, and gene induction methods, among which the chemical induction (angiotensin II, elastase, calcium chloride, beta aminopropionitrile) models are mainly used to study the pathogenesis ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…The development of AAA is related to a focal dilatation of the abdominal aorta measuring 50% greater than the normal proximal segment or >3 cm in maximum diameter. The progression of AAA can lead to aneurysm rupture, an event that reaches 60–80% of mortality [ 11 , 12 , 13 , 14 , 15 ]. In turn, CVD is defined as a syndrome of chronic morphological and functional abnormalities in the venous circulation of the lower extremities, resulting from venous valve incompetence, venous reflux, and venous hypertension [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%